Zoneamento agroclimático do estado de Mato Grosso para produção de sementes de soja de cultivares precoces - Neres, Dielle Carmo de Carvalho (2016)
The goals in this paper were to perform an agroclimatic zoning, identifying the physical, physiological and sanitary attribute, to determine the responsible factors for the reductions of quality and to point the regions with the best climate conditions to produce high-quality soybean seeds from precocious cultivars within the State of Mato Grosso. Regarding the agroclimatic zoning, the geographical information system ArcGIS was used to build a thematic map. The temperature range was divided into three classes, from bigger to smaller, climate risk: Favorable (< 24 °C); Averagely Favorable (24,1 °C a 25 °C); Poorly Favorable (> 25,1 °C). In the harvest of 2012/2013, 341 samples were collected from 16 seed producing companies from different parts of State, totalizing 18 precocious cultivars. Now in the harvest of 2013/2014, 487 seeds sample collected from 17 companies from 28 soy precocious cultivars under evaluation. The physique attribute was evaluated base on the water quantity, the mass of thousand seeds and the percentage of greenish seeds. The physiological attribute was evaluated by the germination tests (first count and final germination), the sprouting of plantlets in the field and tetrazolium test (vitality, viability and damage by bug and mechanical and humidity deterioration) . The sanitary atribute was evaluated by the paper filter method and also by the percentage of seeds with purpura spots. It was conducted and descriptive data analyses and boxplot chart was put together. The characterization of the disposal factors was determined by the germination test, the vitality test, first count, sprouting of plantlets in the field, the tetrazolium test and the determinations of greenish and purpura spotted seeds. The statistical analysis was done by the SPSS program and applied the correlation analysis and linear regression, in addition to determining the correlation coefficients (r) and the determination (R2) between the different variants results of the study. To identify the best regions for seed producing, it was made an analysis comparing the results of the tests of quality of the seeds with the producing regions with higher and lower climatic risk in relation to temperature. Using the obtained results, It was possible to verify that the greater part of the Southeast and West are classified as favorable for the production of soybean seeds of early cultivars. The soybean seeds from precocious cultivars produced in 2013/2014 showed greater vitality than the ones produced in 2012/2013. The physiological attribute in samples that came from the West of the state of Mato Grosso was greater than the other samples from the other regions of the state. In 2012/2013, there was a higher incidence of pathogens in comparison to 2013/2014. The deterioration for humidity followed by mechanical damages were the main reason for the quality drop in the seeds from precocious cultivars. The zones classified as favorable for the producing of soybean seed in precocious cultivars, based on average temperature, showed the best results in seed quality.